ANALISIS MOTIVASI PECINTA KULINER MAKANAN TRADISIONAL DI KOTA SEMARANG - Krisnawati Setyaningrum Nugraheni; Tuwuh Adhistyo Wijoyo (Jurnal Pariwisata Pesona, 2021)
Traditional food is food that is formed by a process of development that lasts for years, because of the fear of being abandoned by the younger generation, forgetting and refusing to consume traditional food which has existed before. So the purpose of this study is to determine the factors that influence the motivation of traditional food culinary lovers in Semarang City. The data analysis technique used is descriptive statistics and factor analysis using the SPSS 25 program. Based on the results of the research that has been done, the following conclusions can be drawn. The motivational factors for choosing food for traditional food culinary lovers in the city of Semarang by using 400 respondents can be drawn the following conclusions, namely, there are six determining factors that can be seen from the highest loading factor of each formed factor. These factors are natural ingredients factors, sensory attractiveness factors, price, mood factors, healthy food factors, and familiarity factors. The dominant factor of motivation for choosing food for traditional food culinary lovers is the natural content factor.